Assessment of Antibiotic Residues in the Marketed Meat of Kailali and Kavre of Nepal - Raut, Rabin; Mandal, Ram Kumar; Kaphle, Krishna; Pant, Dinesh; Nepali, Suresh; Shrestha, Arbindra (International Journal of Applied Sciences and Biotechnology, 2017)
This is a cross-sectional study to detect presence of antibiotic residues in meat sample of Kailali and Kavre districts. Each sample out of 55 meat samples (muscles and liver) of poultry-41, goat-12, buffalo-9 and pig-4 from Kailali and Kavre was tested for different groups of antibiotic residues separately. The antibiotics tested were Penicillin, Tetracycline, Aminoglycosides, Macrolides and Sulfonamides. Samples were preserved at -84˚C in the deep freezer after collecting in sterile plastic pouch. Rapid test kit (78.9% sensitivity and 96.7% specificity) of G9 Co. Ltd., Thailand was used to detect residues in the samples. The protocol of kit was followed for the test. The overall prevalence of antibiotic residues in meat was around 22%. Meat samples exceeding the Maximum Residue Limit (MRL) were 6. Liver was found with higher number of residues than muscles. The organ and location wise prevalence of residue was found statistically significant at p<0.05. The samples contained alarmingly high level of antibiotic residues which is because of neglecting the withdrawal period. The prescription of antibiotic is not prudent. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 386-389